2018
DOI: 10.1093/nar/gky355
|View full text |Cite
|
Sign up to set email alerts
|

LitVar: a semantic search engine for linking genomic variant data in PubMed and PMC

Abstract: The identification and interpretation of genomic variants play a key role in the diagnosis of genetic diseases and related research. These tasks increasingly rely on accessing relevant manually curated information from domain databases (e.g. SwissProt or ClinVar). However, due to the sheer volume of medical literature and high cost of expert curation, curated variant information in existing databases are often incomplete and out-of-date. In addition, the same genetic variant can be mentioned in publications wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 27 publications
1
89
0
Order By: Relevance
“…After invoking variant2literature on 2,277 variants against the 206 papers, 3,011 pairs were reported as positives, resulting a recall rate of 90.86% and a precision rate of 97.08%. For comparison, we performed the same query of variant set on LitVar [4]. By uploading the 2,277 variants to LitVar, 1,138 pairs were reported as positives, resulting a recall rate of 32.76% and a precision rate of 92.62%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After invoking variant2literature on 2,277 variants against the 206 papers, 3,011 pairs were reported as positives, resulting a recall rate of 90.86% and a precision rate of 97.08%. For comparison, we performed the same query of variant set on LitVar [4]. By uploading the 2,277 variants to LitVar, 1,138 pairs were reported as positives, resulting a recall rate of 32.76% and a precision rate of 92.62%.…”
Section: Resultsmentioning
confidence: 99%
“…The annotation of variants involves a critical step that finds literature to explain the potential influence of a discovered variant on protein functions, cell behaviors, organ normality, etc. In this regard, many efforts have been made to improve the search performance [4,5]. Even though, we observed that the sensitivity of variant queries still has space to increase.…”
Section: Introductionmentioning
confidence: 84%
“…LitVar a semantic search engine is proposed by Allott et al [12]. The search engine is used to search the genome related data in the database.…”
Section: Related Workmentioning
confidence: 99%
“…NER is followed by a normalization step mapping the entities to a fixed set of identifiers, such as HGNC gene symbols [Yates et al, 2017] or Disease Ontology terms [Kibbe et al, 2015]. General approaches such as LINNAEUS [Gerner et al, 2010], Tagger [Pafilis et al, 2013], taggerOne [Leaman and Lu, 2016], or OGER [Basaldella et al, 2017] recognize diverse biomedical entities in text, while specialized tools recognize mentions of genetic variants [Allot et al, 2018] or chemicals [Jessop et al, 2011].…”
Section: Introductionmentioning
confidence: 99%